2008
DOI: 10.1080/00207140802463674
|View full text |Cite
|
Sign up to set email alerts
|

Positive Affect, Negative Affect, and Negative Effects During a Phenomenological Hypnotic Assessment Within a Substance Abuse Population

Abstract: Positive and negative affect generated while using the Phenomenology of Consciousness--Hypnotic Assessment Procedure (PCI-HAP) on a sample of drug and alcohol users were predicted using several variables. The results were then cross-validated on a second, smaller sample. The results suggest that, although some negative affect was reported, the PCI-HAP was more likely to generate positive, rather than negative, affect. Positive affect was related to the vividness of a suggested hypnotic dream during hypnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Those assigned to the hypnosis intervention were administered the Harvard Group Scale of Hypnotic Susceptibility to track whether symptom improvement is associated with hypnotizability (Iglesias & Iglesias, 2008;Lichtenberg, Shapira, Kalish, & Abramowitz, 2009;Nash et al, 2009;Oneal, Patterson, Soltani, Teeley, & Jensen, 2008;Pyun & Kim, 2008;Raz, 2008;Wagstaff, Cole, & Brunas-Wagstaff, 2008;Whitehead, Noller, & Sheehan, 2008;Xu & Cardeña, 2008;Yard, DuHamel, & Galynker, 2008). The authors include a host of measures to detect changes in cognition and coping strategies sometimes associated with hypnotic interventions (Karlin, Hill, & Messer, 2008;Nathanson, 2009;Pekala et al, 2008;Pyun & Kim, 2009;Robertson, 2009aRobertson, , 2009bSala et al, 2008;Szendi et al, 2009;Tschugguel & Hunter, 2008). Standardized scales as well as pain diaries were used at baseline and during three treatment phase intervals.…”
Section: Journal: Health Psychologymentioning
confidence: 99%
“…Those assigned to the hypnosis intervention were administered the Harvard Group Scale of Hypnotic Susceptibility to track whether symptom improvement is associated with hypnotizability (Iglesias & Iglesias, 2008;Lichtenberg, Shapira, Kalish, & Abramowitz, 2009;Nash et al, 2009;Oneal, Patterson, Soltani, Teeley, & Jensen, 2008;Pyun & Kim, 2008;Raz, 2008;Wagstaff, Cole, & Brunas-Wagstaff, 2008;Whitehead, Noller, & Sheehan, 2008;Xu & Cardeña, 2008;Yard, DuHamel, & Galynker, 2008). The authors include a host of measures to detect changes in cognition and coping strategies sometimes associated with hypnotic interventions (Karlin, Hill, & Messer, 2008;Nathanson, 2009;Pekala et al, 2008;Pyun & Kim, 2009;Robertson, 2009aRobertson, , 2009bSala et al, 2008;Szendi et al, 2009;Tschugguel & Hunter, 2008). Standardized scales as well as pain diaries were used at baseline and during three treatment phase intervals.…”
Section: Journal: Health Psychologymentioning
confidence: 99%
“…After completing the study, we searched the literature for other studies reporting worries about loss of control. Anxiety and panic, which may represent a perceived loss of control, have been reported as adverse effects of hypnosis in other studies (e.g., Pekala et al, 2008). Kluft (2012) reported that some participants in hypnosis workshops experience difficulties alerting from hypnosis, which can also be conceptualized as a type of loss of control.…”
Section: Discussionmentioning
confidence: 93%